POTENSI PROBIOTIK SEBAGAI REGULATOR SITOKIN INFLAMASI DALAM PERBAIKAN KLINIS PASIEN COVID-19 - WILLIAM SUCIANGTO; Ahmad Taufik Fadillah Zainal; Nada Indira Ramadhani Nasrum (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2022)
ABSTRACT Coronavirus disease 2019 (COVID-19) is a global pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Several recent studies have shown that cytokine storm, robust viral replication, and delayed Interferon type 1 (IFN-I) signaling contribute to the severity of COVID-19 . The slow response of IFN-I leads to the increased accumulation of pathogenic monocytes resulting in pulmonary immunopathology, vascular leakage, and suboptimal T cell response. In addition, other studies have reported that administration of probiotics can mediate antiviral responses against human coronavirus. We discuss about the potential of probiotics to regulate cytokine storms and the production of type-1 Interferon that implicates to clinical improvement in COVID-19 patients. This review is made from the results of a qualitative synthesis from various valid sources. The results show that several types of probiotics can supress the production of pro-inflammatory cytokines involved in cytokine storms and enhance the production of type-1 IFN. Through the mechanism of preventing cytokine storms and increasing type-1 production, probiotics are expected to become a regulator of immune system that can improve clinical performance in COVID-19 patients. Although further detailed research on a larger scale is still required to prove that probiotics can be a solution for the treatment of viral infections.